PENGARUH BELANJA MODAL DAN PENDAPATAN ASLI DAERAH (PAD) TERHADAP PERTUMBUHAN EKONOMI DI WILAYAH KALIMANTAN - B01108128, Siesa Sitorus (Jurnal Pembangunan dan Pemerataan, 2013)
The research was conducted to determine the effect of capital expenditure and revenue (PAD) on economic growth in the region of Borneo. The tools used in this research is to use panel data regression analysis model (cross section and time series), with the data observation many as 36 in the fourth province of Kalimantan region over the period 2003-2011. The processing of the data using computer program Eviews-6. Based on calculations, the results of the regression and the various tests that have been done indicate that simultaneous capital expenditure and revenue (PAD) a significant effect on economic growth in the region of Borneo. Partially, capital expenditures exert a negative impact on economic growth in the region of Borneo, while the Revenue have a positive influence on economic growth in the region of Borneo. Keywords: Economic Growth, Capital Expenditure and revenue (PAD)